Implementation of exome sequencing for rare undiagnosed diseases in LMICs: the G2MC rare diseases exome sequencing pilot project - Yasas D. Kolambage; Claudia Gonzaga-Jauregui; Guillermo Lay-Son; Rupesh Mishra; Njabulo Christian Mabaso; Sok-Kun Tae; Kristin A. Maloney; Carolina I. Galaz-Montoya; Dineshani Hettiarachchi; Bronwyn Dillon; Nilam Thakur; Ludivine de Menten; et al. (Human Genetics, 2026)

Lynch syndrome caused by a pathogenic SINE-VNTR-Alu (SVA) insertion in MSH2 gene identified by long-read DNA sequencing - Jihoon E. Joo; Khalid Mahmood; Mark Clendenning; Peter Georgeson; Romy Walker; Julia Como; Fiona Phillips; Bernard J. Pope; Steven Batinovic; Natalie Diepenhorst; Julie McDonald; Toni Rice; et al. (Familial Cancer, 2026)
Lynch syndrome, the most common hereditary cancer syndrome, is caused by germline pathogenic variants in DNA mismatch repair (MMR) genes. Identifying complex or structural MMR gene pathogenic variants can be challenging with short-read sequencing resulting in patients with unexplained MMR-deficient tumours. In this study, we report multiple members of a family who developed MSH2-deficient tumours where clinical multi-gene panel testing of the DNA MMR genes using short-read sequencing did not find a germline pathogenic variant. Oxford Nanopore Technologies adaptive sampling (ONT-AS) long-read sequencing, targeting 104 hereditary cancer genes, identified a shared ~ 3.2 kb SINE-VNTR-Alu (SVA) family F retrotransposon insertion within exon 12 of MSH2 in both the proband and her father. Segregation of this MSH2 SVA insertion by targeted PCR confirmed three additional family members as carriers, including a paternal uncle with three colorectal cancers and an MSH2-deficient sebaceous adenoma. Three of the five heterozygous carriers were cancer affected with at least one MSH2-deficient tumour each. This study demonstrates that long-read sequencing can identify structural variants that are missed by current short-read sequencing multi-gene panel testing, improving the diagnosis of Lynch syndrome. These findings support incorporating long-read sequencing into routine diagnostic workflows for patients with suspected Lynch syndrome following a negative germline test.

Humanisierung steigert die Wirksamkeit von CAR-T-Zelltherapien - Tobias D. Deller; Toni Cathomen (BIOspektrum, 2026)
Chimeric Antigen Receptor (CAR) T cells are among the most promising cancer therapeutics of the past decade. However, immunogenic components, often of murine origin, can elicit anti-CAR immune responses that limit their persistence and efficacy. “Humanization” replaces murine sequences with human counterparts, reducing immunogenicity while preserving function. This article discusses mechanisms of CAR T cell rejection and the clinical potential of humanized CAR designs.

Global and regional conservation status of vascular wetland plants in Mediterranean islands: a collaborative network to improve knowledge and awareness - Mauro Fois; Carles Burguera; Necmi Aksoy; Gianluigi Bacchetta; Simonetta Bagella; Giulio Barone; Ioannis Bazos; Imtinen Ben Haj Jilani; Leanne Camilleri; Miquel Capó; Charalambos S. Christodoulou; Amina Daoud-Bouattour; et al. (Biological Conservation, 2026)

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Quest for Orthologs in the era of Data Deluge and AI: Challenges and Innovations in Orthology Prediction and Data Integration - Sina Majidian; Armin Hadziahmetovic; Felix Langschied; Stefano Pascarelli; Silvia Prieto-Baños; Jorge Rojas-Vargas; Lars Arvestad; Jitender Cheema; Salvatore Cosentino; Ingo Ebersberger; Elena Kuzmin; Yannis Nevers; et al. (Journal of Molecular Evolution, 2025)
The rapid advancement of DNA sequencing technologies and computational algorithms has led to an unprecedented surge in genomic data, driven by several large-scale sequencing projects worldwide. Orthology plays a crucial role in understanding evolutionary patterns of genes and their functions. At the last Quest for Orthologs meeting (Montréal, Canada—2024), we discussed recent advances in orthology inference, with a focus on the impact of artificial intelligence (AI), protein structures, RNA splicing isoforms, and protein domain evolution together with other evolutionary considerations. A long-standing challenge in the field is the functional annotation of paralogs, for which we present novel approaches. The meeting also emphasised strategies for integrating diverse genetic features into the concept of orthology, encouraging frameworks that account for elements like alternative splicing, domain organisation, and regulatory sequences. We discuss various applications of orthology and paralogy to environmental research, agriculture, and comparative genomics. Additionally, we report recent progress in orthology inference methodologies and resources. This work represents a collaborative synthesis of insights and innovations presented at the 8th Quest for Orthologs meeting, highlighting current progress while outlining future directions for orthology research.

Controls on storage capacity in mudstones. Cementation before sediment compaction and preservation of porosity in lithified rock - Daniel Minisini; Toni Simo; Joe H.S. Macquaker; Mark D. Rudnicki (Marine and Petroleum Geology, 2025)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Identifying new invasive plants in the face of climate change: a focus on sleeper species - Ayodele C. O’Uhuru; Toni Lyn Morelli; Annette E. Evans; Justin D. Salva; Bethany A. Bradley (Biological Invasions, 2024)

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

Investigating impacts of the mycothiazole chemotype as a chemical probe for the study of mitochondrial function and aging - Naibedya Dutta; Joe A. Gerke; Sofia F. Odron; Joseph D. Morris; Adam Hruby; Juri Kim; Toni Castro Torres; Sarah J. Shemtov; Jacqueline G. Clarke; Michelle C. Chang; Hooriya Shaghasi; Marissa N. Ray; et al. (GeroScience, 2024)
Small molecule inhibitors of the mitochondrial electron transport chain (ETC) hold significant promise to provide valuable insights to the field of mitochondrial research and aging biology. In this study, we investigated two molecules: mycothiazole (MTZ) - from the marine sponge C. mycofijiensis and its more stable semisynthetic analog 8- O -acetylmycothiazole (8-OAc) as potent and selective chemical probes based on their high efficiency to inhibit ETC complex I function. Similar to rotenone (Rote), MTZ, a newly employed ETC complex I inhibitor, exhibited higher cytotoxicity against cancer cell lines compared to certain non-cancer cell lines. Interestingly, 8-OAc demonstrated greater selectivity for cancer cells when compared to both MTZ and Rote, which has promising potential for anticancer therapeutic development. Furthermore, in vivo experiments with these small molecules utilizing a C. elegans model demonstrate their unexplored potential to investigate aging studies. We observed that both molecules have the ability to induce a mitochondria-specific unfolded protein response (UPR MT ) pathway, that extends lifespan of worms when applied in their adult stage. We also found that these two molecules employ different pathways to extend lifespan in worms. Whereas MTZ utilizes the transcription factors ATFS-1 and HSF1, which are involved in the UPR MT and heat shock response (HSR) pathways respectively, 8-OAc only required HSF1 and not ATFS-1 to mediate its effects. This observation underscores the value of applying stable, potent, and selective next generation chemical probes to elucidate an important insight into the functional roles of various protein subunits of ETC complexes and their regulatory mechanisms associated with aging. Graphical Abstract

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

No evidence for tropicalization of coral assemblages in a subtropical climate change hot spot - Toni L. Mizerek; Joshua S. Madin; Francesca Benzoni; Danwei Huang; Osmar J. Luiz; Hanaka Mera; Sebastian Schmidt-Roach; Stephen D. A. Smith; Brigitte Sommer; Andrew H. Baird (Coral Reefs, 2021)

Beyond ecosystem modeling: A roadmap to community cyberinfrastructure for ecological data‐model integration - Istem Fer; Anthony K. Gardella; Alexey N. Shiklomanov; Eleanor E. Campbell; Elizabeth M. Cowdery; Martin G. De Kauwe; Ankur Desai; Matthew J. Duveneck; Joshua B. Fisher; Katherine D. Haynes; Forrest M. Hoffman; Miriam R. Johnston; et al. (Global Change Biology, 2021)
In an era of rapid global change, our ability to understand and predict Earth's natural systems is lagging behind our ability to monitor and measure changes in the biosphere. Bottlenecks to informing models with observations have reduced our capacity to fully exploit the growing volume and variety of available data. Here, we take a critical look at the information infrastructure that connects ecosystem modeling and measurement efforts, and propose a roadmap to community cyberinfrastructure development that can reduce the divisions between empirical research and modeling and accelerate the pace of discovery. A new era of data‐model integration requires investment in accessible, scalable, and transparent tools that integrate the expertise of the whole community, including both modelers and empiricists. This roadmap focuses on five key opportunities for community tools: the underlying foundations of community cyberinfrastructure; data ingest; calibration of models to data; model‐data benchmarking; and data assimilation and ecological forecasting. This community‐driven approach is a key to meeting the pressing needs of science and society in the 21st century.

Vulnerability of rangeland beef cattle production to climate‐induced NPP fluctuations in the US Great Plains - Toni Klemm; David D. Briske; Matthew C. Reeves (Global Change Biology, 2020)
The vulnerability of rangeland beef cattle production to increasing climate variability in the US Great Plains has received minimal attention in spite of potentially adverse socioeconomic and ecological consequences. Vulnerability was assessed as the frequency and magnitude of years in which net primary production (NPP) deviated >±25% from mean values, to represent major forage surplus and deficit years, for a historic reference period (1981–2010), mid‐century (2041–2065), and late‐century (2075–2099) periods. NPP was simulated by MC2, a dynamic global vegetation model, driven by five climate projections for representative concentration pathway (RCP) 4.5 and 8.5. Historically, 4–4.7 years per decade showed either NPP surpluses or deficits. The future number of extreme years increased to 5.4–6.4 and 5.9–6.9 per decade for RCP 4.5 and 8.5, respectively, which represents an increase of 33%–56% and 38%–73%, respectively. Future simulations exhibited increases in surplus years to between 3 and 5 years in the Northern Plains and 3–3.5 in the Southern Plains. The number of deficit years remained near historic values of 2 in the Northern Plains, but increased in the Southern Plains from 2.5 to 3.3 per decade. Historically, NPP in extreme surplus and deficit years both deviated 40% from mean NPP in all three regions. The magnitude of deficit years increased by 6%–17% in future simulations for all three regions, while the magnitude of surplus years decreased 16% in the Northern Plains and increased 16% in the Southern Plains. The Southern Plains was the only region to exhibit an increase in the magnitude of both surplus and deficit years. Unprecedented future variability of NPP may surpass the existing adaptive capacity of beef producers and adversely impact the economic viability of rangeland cattle production and ecological sustainability of rangeland resources.

C-peptide corrects hepatocellular dysfunction in a rat model of type 1 diabetes - Heba A. Abdel-Hamid; Elshymaa A. Abdel-Hakeem; Nagwa M. Zenhom; Nisreen D. M. Toni (Journal of Physiology and Biochemistry, 2020)

Correction to: PRSS21/testisin inhibits ovarian tumor metastasis and antagonizes proangiogenic angiopoietins ANG2 and ANGPTL4 - Gregory D. Conway; Marguerite S. Buzza; Erik W. Martin; Nadire Duru; Tierra A. Johnson; Raymond J. Peroutka; Nisha R. Pawar; Toni M. Antalis (Journal of Molecular Medicine, 2019)

PRSS21/testisin inhibits ovarian tumor metastasis and antagonizes proangiogenic angiopoietins ANG2 and ANGPTL4 - Gregory D. Conway; Marguerite S. Buzza; Erik W. Martin; Nadire Duru; Tierra A. Johnson; Raymond J. Peroutka; Nisha R. Pawar; Toni M. Antalis (Journal of Molecular Medicine, 2019)

Phenological sensitivity to climate change is higher in resident than in migrant bird populations among European cavity breeders - Jelmer M. Samplonius; Lenka Bartošová; Malcolm D. Burgess; Andrey V. Bushuev; Tapio Eeva; Elena V. Ivankina; Anvar B. Kerimov; Indrikis Krams; Toni Laaksonen; Marko Mägi; Raivo Mänd; Jaime Potti; et al. (Global Change Biology, 2018)
Many organisms adjust their reproductive phenology in response to climate change, but phenological sensitivity to temperature may vary between species. For example, resident and migratory birds have vastly different annual cycles, which can cause differential temperature sensitivity at the breeding grounds, and may affect competitive dynamics. Currently, however, adjustment to climate change in resident and migratory birds have been studied separately or at relatively small geographical scales with varying time series durations and methodologies. Here, we studied differential effects of temperature on resident and migratory birds using the mean egg laying initiation dates from 10 European nest box schemes between 1991 and 2015 that had data on at least one resident tit species and at least one migratory flycatcher species. We found that both tits and flycatchers advanced laying in response to spring warming, but resident tit populations advanced more strongly in relation to temperature increases than migratory flycatchers. These different temperature responses have already led to a divergence in laying dates between tits and flycatchers of on average 0.94 days per decade over the current study period. Interestingly, this divergence was stronger at lower latitudes where the interval between tit and flycatcher phenology is smaller and winter conditions can be considered more favorable for resident birds. This could indicate that phenological adjustment to climate change by flycatchers is increasingly hampered by competition with resident species. Indeed, we found that tit laying date had an additional effect on flycatcher laying date after controlling for temperature, and this effect was strongest in areas with the shortest interval between both species groups. Combined, our results suggest that the differential effect of climate change on species groups with overlapping breeding ecology affects the phenological interval between them, potentially affecting interspecific interactions.

Vegetation demographics in Earth System Models: A review of progress and priorities - Rosie A. Fisher; Charles D. Koven; William R. L. Anderegg; Bradley O. Christoffersen; Michael C. Dietze; Caroline E. Farrior; Jennifer A. Holm; George C. Hurtt; Ryan G. Knox; Peter J. Lawrence; Jeremy W. Lichstein; Marcos Longo; et al. (Global Change Biology, 2018)
Numerous current efforts seek to improve the representation of ecosystem ecology and vegetation demographic processes within Earth System Models ( ESM s). These developments are widely viewed as an important step in developing greater realism in predictions of future ecosystem states and fluxes. Increased realism, however, leads to increased model complexity, with new features raising a suite of ecological questions that require empirical constraints. Here, we review the developments that permit the representation of plant demographics in ESM s, and identify issues raised by these developments that highlight important gaps in ecological understanding. These issues inevitably translate into uncertainty in model projections but also allow models to be applied to new processes and questions concerning the dynamics of real‐world ecosystems. We argue that stronger and more innovative connections to data, across the range of scales considered, are required to address these gaps in understanding. The development of first‐generation land surface models as a unifying framework for ecophysiological understanding stimulated much research into plant physiological traits and gas exchange. Constraining predictions at ecologically relevant spatial and temporal scales will require a similar investment of effort and intensified inter‐disciplinary communication.

Determinants of cancer screening in Asian-Americans - Quoc-Dien Trinh; Hanhan Li; Christian P. Meyer; Julian Hanske; Toni K. Choueiri; Gally Reznor; Stuart R. Lipsitz; Adam S. Kibel; Paul K. Han; Paul L. Nguyen; Mani Menon; Jesse D. Sammon (Cancer Causes & Control, 2016)

A Role for Volatiles in Intra- and Inter-Plant Interactions in Birch - P. Sarai Girón-Calva; Tao Li; Tuuli-Marjaana Koski; Tero Klemola; Toni Laaksonen; Liisa Huttunen; James D. Blande (Journal of Chemical Ecology, 2014)

Fire Management, Managed Relocation, and Land Conservation Options for Long‐Lived Obligate Seeding Plants under Global Changes in Climate, Urbanization, and Fire Regime - TIMOTHY C. BONEBRAKE; ALEXANDRA D. SYPHARD; JANET FRANKLIN; KURT E. ANDERSON; H. RESIT AKÇAKAYA; TONI MIZEREK; CLARK WINCHELL; HELEN M. REGAN (Conservation Biology, 2014)
Most species face multiple anthropogenic disruptions. Few studies have quantified the cumulative influence of multiple threats on species of conservation concern, and far fewer have quantified the potential relative value of multiple conservation interventions in light of these threats. We linked spatial distribution and population viability models to explore conservation interventions under projected climate change, urbanization, and changes in fire regime on a long‐lived obligate seeding plant species sensitive to high fire frequencies, a dominant plant functional type in many fire‐prone ecosystems, including the biodiversity hotspots of Mediterranean‐type ecosystems. First, we investigated the relative risk of population decline for plant populations in landscapes with and without land protection under an existing habitat conservation plan. Second, we modeled the effectiveness of relocating both seedlings and seeds from a large patch with predicted declines in habitat area to 2 unoccupied recipient patches with increasing habitat area under 2 projected climate change scenarios. Finally, we modeled 8 fire return intervals (FRIs) approximating the outcomes of different management strategies that effectively control fire frequency. Invariably, long‐lived obligate seeding populations remained viable only when FRIs were maintained at or above a minimum level. Land conservation and seedling relocation efforts lessened the impact of climate change and land‐use change on obligate seeding populations to differing degrees depending on the climate change scenario, but neither of these efforts was as generally effective as frequent translocation of seeds. While none of the modeled strategies fully compensated for the effects of land‐use and climate change, an integrative approach managing multiple threats may diminish population declines for species in complex landscapes. Conservation plans designed to mitigate the impacts of a single threat are likely to fail if additional threats are ignored. Manejo de Incendios, Reubicación Administrada y Opciones de Conservación de Suelo para Plantas de Vida Larga con Sembrado Obligado bajo los Cambios Globales en el Clima, la Urbanización y el Régimen de Incendios

PALEOMAGIA: A PHP/MYSQL database of the Precambrian paleomagnetic data - Toni Veikkolainen; Lauri J. Pesonen; David A. D. Evans (Studia Geophysica et Geodaetica, 2014)

Physiological and Behavioral Effects of Capture Darting on Red Colobus Monkeys (Procolobus rufomitratus) with a Comparison to Chimpanzee (Pan troglodytes) Predation - Michael D. Wasserman; Colin A. Chapman; Katharine Milton; Tony L. Goldberg; Toni E. Ziegler (International Journal of Primatology, 2013)

The Fecal Odor of Sick Hedgehogs (Erinaceus europaeus) Mediates Olfactory Attraction of the Tick Ixodes hexagonus - Toni Bunnell; Kerstin Hanisch; Jörg D. Hardege; Thomas Breithaupt (Journal of Chemical Ecology, 2011)

Terrestrial Biodiversity Analyses in Dalmatia (Croatia): A Complementary Approach Using Diversity and Rarity - Sven D. Jelaska; Toni Nikolić; Lucija Šerić Jelaska; Vladimir Kušan; Hrvoje Peternel; Goran Gužvica; Zoran Major (Environmental Management, 2010)

Glucokinase regulatory protein gene polymorphism affects postprandial lipemic response in a dietary intervention study - Haiqing Shen; Toni I. Pollin; Coleen M. Damcott; John C. McLenithan; Braxton D. Mitchell; Alan R. Shuldiner (Human Genetics, 2009)

URban Biotopes of Aotearoa New Zealand (URBANZ) (I): composition and diversity of temperate urban lawns in Christchurch - Glenn H. Stewart; Maria E. Ignatieva; Colin D. Meurk; Hannah Buckley; Benjamin Horne; Toni Braddick (Urban Ecosystems, 2009)

UTP and ATP increase extracellular signal-regulated kinase 1/2 phosphorylation in bovine chromaffin cells through epidermal growth factor receptor transactivation - Toni M. Luke; Terry D. Hexum (Purinergic Signalling, 2008)

Antibiotic and Disinfectant Susceptibility Profiles of Vancomycin-Resistant Enterococcus faecium (VRE) Isolated from Community Wastewater in Texas - Ross C. Beier; Sara E. Duke; Richard L. Ziprin; Roger B. Harvey; Michael E. Hume; Toni L. Poole; H. Morgan Scott; Linda D. Highfield; Walid Q. Alali; Kathleen Andrews; Robin C. Anderson; David J. Nisbet (Bulletin of Environmental Contamination and Toxicology, 2008)

Membrane anchored serine proteases: A rapidly expanding group of cell surface proteolytic enzymes with potential roles in cancer - Sarah Netzel-Arnett; John D. Hooper; Roman Szabo; Edwin L. Madison; James P. Quigley; Thomas H. Bugge; Toni M. Antalis (Cancer and Metastasis Reviews, 2003)